2023
DOI: 10.1037/adb0000871
|View full text |Cite
|
Sign up to set email alerts
|

Constructs derived from the addiction cycle predict alcohol use disorder treatment outcomes and recovery 3 years following treatment.

Abstract: Objective: The addiction cycle has been proposed as a framework for understanding the progression of alcohol use disorder (AUD) in terms of psychological and biological domains, including reward drinking/incentive salience, relief drinking/negative emotionality, and loss of control/executive functioning impairment. To have utility in clinical practice, self-report measures of these domains that are applicable across sociodemographic groups and associated with clinical outcomes are needed. This study sought to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
40
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(46 citation statements)
references
References 69 publications
6
40
0
Order By: Relevance
“…In fact, by blurring the distinction between dispositional and acquired features, we might attenuate observed associations between negative emotionality and drinking-related outcomes, given that the link between dispositional negative emotionality and alcohol use disorder is relatively weak (Hussong et al, 2011). Only one study has examined the ANA domains using alcohol-specific indicators, and findings showed the utility of these domains for predicting treatment outcomes one and three years following treatment (Witkiewitz, Stein, et al, 2022). An essential step in refining ANA measurement will be examining whether alcohol-specific, specifically acquired, or general indicators of the three ANA domains are more valid or meaningful.…”
Section: Limitations Of Prior Evaluations Of the Addictions Neuroclin...mentioning
confidence: 99%
See 4 more Smart Citations
“…In fact, by blurring the distinction between dispositional and acquired features, we might attenuate observed associations between negative emotionality and drinking-related outcomes, given that the link between dispositional negative emotionality and alcohol use disorder is relatively weak (Hussong et al, 2011). Only one study has examined the ANA domains using alcohol-specific indicators, and findings showed the utility of these domains for predicting treatment outcomes one and three years following treatment (Witkiewitz, Stein, et al, 2022). An essential step in refining ANA measurement will be examining whether alcohol-specific, specifically acquired, or general indicators of the three ANA domains are more valid or meaningful.…”
Section: Limitations Of Prior Evaluations Of the Addictions Neuroclin...mentioning
confidence: 99%
“…Further, although self-report indicators increase the feasibility of the ANA battery in clinical practice by reducing the burden on clinicians and clients, the indicators evaluated thus far have several limitations that hinder interpretability (Boness et al, 2021;Witkiewitz, Stein, et al, 2022). Previous studies have used a wide range of indicators, including many general or trait measures of reward/incentive salience, negative emotionality, and cognitive control/executive function that were not designed to assess core AUD mechanisms and do not reflect the intention of the ANA to measure constructs reflecting the addiction cycle (Boness et al, 2021;Witkiewitz, Stein, et al, 2022).…”
Section: Limitations Of Prior Evaluations Of the Addictions Neuroclin...mentioning
confidence: 99%
See 3 more Smart Citations